Determination of the local geoid ellipsiod separation - A case study of Tarkwa and its environs - Boye, C.B.; Yakubu, I (University of Mines and Technology, 2010)
Although satellite-based positioning techniques, especially Global Positioning System (GPS) are used extensively in Ghana together with the conventional methods of positioning fixing, there is little information about the geoid-ellipsoid separation (N), a parameter required to transform measured ellipsoidal heights to the locally used geoidal heights for constructional purposes. This deficiency compels users of GPS in the country to accept the default value (zero) offered by their respective software developers during post processing of GPS data, which results in relatively lower accuracy in height measurement. To overcome this challenge and to enable easy conversion of heights from orthometric to ellipsoidal height, this study sought to determine the actual value of N for the study area. Ellipsoidal and geoidal heights were determined for selected points using GPS receivers and trigonometric leveling from which the average separation between the two surfaces was generated from the dataset. The determination of the separation was accomplished with the aid of the Earth Gravitational Model 1996 (EGM96). A plot of the two heights showed strong correlation with the intercept representing the value of N. The most probable value (MPV) of the height differences between the ellipsoidal and the geoidal height yielded 8.40 m where as the line of best fit from a regression analysis of the scatter plot gave 9.07 m with 95% confidence interval. A sensitivity test was carried out using the determined value of N instead of the default value previously used for reprocessing of the GPS data yielded better accuracy of 0.05 mm.
Keywords: Geoid; Ellipsoid